Attitudes towards the integration of smoking cessation into lung cancer screening in the United Kingdom: A qualitative study of individuals eligible to attend. (5th May 2022) - Groves, Samantha; McCutchan, Grace; Quaife, Samantha L.; Murray, Rachael L.; Ostroff, Jamie S.; Brain, Kate; Crosbie, Philip A. J.; Yorke, Janelle; Baldwin, David; Field, John K.; McWilliams, Lorna
Abstract: Introduction: There is limited research exploring how smoking cessation treatment should be implemented into lung cancer screening in the United Kingdom. This study aimed to understand attitudes and preferences regarding the integration of smoking cessation support within lung cancer screening from the perspective of those eligible. Methods: Thirty‐one lung cancer screening eligible individuals aged 55–80 years with current or former smoking histories were recruited using community outreach and social media. Two focus groups (three participants each) and 25 individual telephone interviews were conducted. Data were analysed using the framework approach to thematic analysis. Results: Three themes were generated: (1) bringing lung cancer closer to home, where screening was viewed as providing an opportunity to motivate smoking cessation, depending on perceived personal risk and screening result; (2) a sensitive approach to cessation with the uptake of cessation support considered to be largely dependent on screening practitioners' communication style and expectations of stigma and (3) creating an equitable service that focuses on ease of access as a key determinant of uptake, where integrating cessation within the screening appointment may sustain increased quit motivation and prevent loss to follow‐up. Conclusions: The integration of smoking cessation into lung cancer screening was viewed positively by those eligible to attend. Screening appointments providing personalized lung health information may increase cessation motivation. Services should proactively support participants with possible fatalistic views regarding risk and decreased cessation motivation upon receiving a good screening result. To increase engagement in cessation, services need to be person‐centred. Patient or Public Contribution: This study has included patient and public involvement throughout, including input regarding study design, research materials, recruitment strategies and research summaries.